Uniplanar Versus Fixed Pedicle Screws in the Correction of Thoracic Kyphosis in the Treatment of Adolescent Idiopathic Scoliosis (AIS). Issue 8 (December 2017) - Badve, Siddharth A.; Goodwin, Ryan C.; Gurd, David; Kuivila, Thomas; Kurra, Swamy; Lavelle, William F.
Abstract : Background: The aim of surgical treatment of scoliosis is to obtain fusion of the spinal column, balanced in the coronal and sagittal planes. Great success has been attained with coronal correction; however, the sagittal profile has received less attention, resulting in little correction of sagittal plane alignment. The purpose of this study was to compare uniplanar and fixed pedicle screws in the correction of the thoracic sagittal alignment in the treatment of adolescent idiopathic scoliosis (AIS). Methods: The sagittal profile of 2 groups of patients undergoing posterior spinal fusion (PSF) for AIS was compared. One group had uniplanar screws (n=16) as bone anchors, and the second group had fixed screws (n=20). Consecutive patients with AIS treated by PSF during 2004 to 2006 with fixed screws; and those treated in 2008 with uniplanar screws were included in the study. Data included: patient demographics, medical conditions, curve type, Risser stage, coronal and sagittal curve magnitude, curve flexibility, osteotomies, fusion levels, type and location of instrumentation, curve magnitude at the initial postoperative visit and at final follow-up. ANOVA and χ 2 testing was completed. A P <0.05 was considered significant. Results: Both groups were comparable demographically, medically, in relation to the curve characteristics and the surgical treatment. Immediate postcorrection sagittal curvature measurements were greater using the uniplanar than fixed screws, 36 versus 26 degrees and was also statistically significant at final follow-up ( P =0.006). There was no difference between groups with respect to coronal thoracic deformity. In the Lenke 1 and Lenke 2 curve population, similar results were found. Conclusions: In patients undergoing PSF for AIS, uniplanar screws achieved superior correction of the sagittal thoracic alignment than fixed screws. This advantage was maintained in the postoperative follow-up period. The ability of the uniplanar screws to adapt to variable sagittal orientation appears to contribute to better radiographic outcomes. Level of Evidence: This is a level III respective review study conducted at a single center from a single, pediatric spine surgeon.